Use and perceived effectiveness of complementary health approaches in children. Issue 1 (8th December 2017) - Kalaichandran, Amitha; Barrowman, Nick; Chan, Jason; Toupin-April, Karine; Vohra, Sunita; Zemek, Roger
Abstract: Background and Objectives: Up to one-half of children may use complementary health approaches (CHA). However, current prevalence in North America, variables associated with CHA use and caregiver perceptions of effectiveness are unclear. We aimed to determine the self-reported use of CHA during the previous 12 months in paediatric patients, demographic variables associated with CHA use and perceptions around effectiveness of CHA. Methods: A cross-sectional survey study of patients aged between 28 days and 18 years who presented to a large paediatric emergency department was conducted between December 2014 and July 2015. Univariate analysis and multivariate logistic regression were used to examine variables associated with CHA use. Results: Of 475 potential participants, 412 (86.7%) responded to the questionnaire, of whom 369 (89.5%) had completed the entire survey. Of these, 61.7% (95% confidence interval [CI] 56.7% to 66.6%) reported using CHA for their child. The most used CHA products were vitamins and minerals (59.2%, 95% CI 52.4% to 65.7%). Among CHA practices, massage (50.0%, 95% CI 15.5% to 30.1%) was most common. Most CHA users perceived effectiveness of the therapy used. Parental education remained statistically significant (P=0.03) in multivariate logistic regression; the odds of CHA use among caregivers with university-level education were 1.65 times higher when compared with those without (95% CI 1.04% to 2.61%). Conclusions: CHA use is higher than previously reported in children. Given the high self-reported perceived effectiveness, paediatricians and family physicians should review CHA use with their patients in an open, non-judgmental manner, exploring both perceptions of safety and efficacy.